Bank regulation in dollarized economies: The case of Turkey - Erick W. Rengifo; Emre Ozsoz; Mustapha A. Akinkunmi; Eduardo Court (International Journal of Financial Studies, 2013)
Regulators in emerging markets are increasingly curtailing the practice of foreigncurrency lending. In such a move Turkish regulatory authorities banned foreign currencylending to households in 2009. This paper examines the evolution of financial dollarization inTurkey in the 2002-2009 period by looking the currency composition of loans and deposits inthe banking system and the macroeconomic developments. We find that the Turkish bankingsystem was unhedged against currency fluctuations and the regulators acted preemptively inbanning the practice.
Keywords: 330; dollarization; banking regulation; Turkish banking system